PERISTIWA CAMPUR KODE BERDASARKAN KEMAMPUAN BILINGUALISME DALAM SOSIAL MEDIA: INSTAGRAM DAN TWITTER: Kajian Sosiolinguistik - Shoolihah, Roofidah (Jurnal Pena Indonesia, 2024)
This research aims to find out code-mixing events based on bilingualism ability in terms of socialmedia, namely Instagram and Twitter. The data sources of this research are Instagram posts andTwitter tweets. The data collection technique in this research is the observation technique. The listeningtechnique is to review the Instagram uploads and Twitter tweets, then the note-taking technique is done by recording important data related to the code mix contained in it. The method used is descriptive qualitative method. The results showed that there were code mix events based on people's ability in bilingualism, namely on Instagram uploads in which there were Indonesian and English code mixes on moodreceh.id and folkative accounts and on Twitter account tweets @morkiecan and @BanHestu in which there were Indonesian and Javanese code mixes.